Role of China in Improving the Regional Connectivity and Economic Development in African Union through Program for Infrastructure Development in Africa-Priority Action Plan 1 (PIDA-PAP 1) (2012-2020) - Muhammad Amjad Raza; Dr. Abdul Basit Khan (Remittances Review, 2024)
The Programme for Infrastructure Development in Africa (PIDA) is an initiative of the African Union (AU) Commission taken in collaboration with other AU institutions. The NEPAD Planning and Coordinating Agency (NPCA), the United Nations Economic Commission (UNEC) for Africa, and the African Development Bank (AfDB) partnered with the program. PIDA aims to expedite infrastructure development in Africa and overcome the challenges of regional connectivity. It is divided into two Priority Action Plans (PAP) i.e. 'PIDA-PAP1' and 'PIDA-PAP2'. The PIDA-PAP1 (2012-2020) is a strategic framework which ensures fast-track implementation of various projects to address developmental and integrative issues faced by the AU member states which are chiefly related to energy, transboundary water, transportation, and Information and Communication Technology (ICT) sectors. The current study reviews the nature and quantum of Chinese engagements with AU under the PIDA initiative for continental integration by particularly focussing on PAP 1 Program. It qualitatively analyses the relevant literature including official reports and financial documents to critically understand the extensive nature of Chinese involvement in these projects and finds that China is quite keenly involved within the member states of AU to develop inter- and intra-regional connectivity which is apparently intended and would ultimately be helpful to fulfil her own growing economic needs. The study would be helpful for the scholars, researchers from academia as well as policy-makers and think-tanks working on the China-AU economic relations.
Keywords: Program for Infrastructure Development in Africa; China-African Union Relations; Priority Action Plan 1